Small molecules induce mesocrystal formation: nanoparticle aggregation directed by self-assembling calixarenes - Baynton, A.; Radomirovic, Tomoko; Ogden, Mark; Raston, C.; Richmond, William; Jones, Franca (The Royal Society of Chemistry, 2010)
Calixarenes have been shown to induce mesocrystal formation of barium sulfate, despite being relatively low molecular weight additives. Scanning probe microscopy has shown that a possible mechanism is the self-assembling properties of the calixarene resulting in steric stabilization of the nanoparticles, comparable to that typically requiring polymeric additives.